Cost Associated With Pediatric Delirium in the ICU. Issue 12 (December 2016) - Traube, Chani; Mauer, Elizabeth A.; Gerber, Linda M.; Kaur, Savneet; Joyce, Christine; Kerson, Abigail; Carlo, Charlene; Notterman, Daniel; Worgall, Stefan; Silver, Gabrielle; Greenwald, Bruce M.
Abstract : Objective: To determine the costs associated with delirium in critically ill children. Design: Prospective observational study. Setting: An urban, academic, tertiary-care PICU in New York city. Patients: Four-hundred and sixty-four consecutive PICU admissions between September 2, 2014, and December 12, 2014. Interventions: None. Measurements and Main Results: All children were assessed for delirium daily throughout their PICU stay. Hospital costs were analyzed using cost-to-charge ratios, in 2014 dollars. Median total PICU costs were higher in patients with delirium than in patients who were never delirious ($18, 832 vs $4, 803; p < 0.0001). Costs increased incrementally with number of days spent delirious (median cost of $9, 173 for 1 d with delirium, $19, 682 for 2–3 d with delirium, and $75, 833 for > 3 d with delirium; p < 0.0001); this remained highly significant even after adjusting for PICU length of stay ( p < 0.0001). After controlling for age, gender, severity of illness, and PICU length of stay, delirium was associated with an 85% increase in PICU costs ( p < 0.0001). Conclusions: Pediatric delirium is associated with a major increase in PICU costs. Further research directed at prevention and treatment of pediatric delirium is essential to improve outcomes in this population and could lead to substantial healthcare savings.